Comparing Clinical Outcomes of Early and Elective Reconstruction in Patients with Anterior Cruciate Ligament Tears - Wutphiriyaangkun, Sombun (Journal of Southeast Asian Orthopaedics, 2023)
Purpose: The optimal time of treatment for anterior cruciate ligament tears remains controversial. Two times are early (< 6 weeks) and elective (≥ 6 weeks) reconstruction. This retrospective study tested the hypothesis that clinical outcomes are similar between the two time groups for anterior cruciate ligament reconstruction. Methods: A total of 61 patients were included in this study. Thirty and 31 patients were in the early and elective reconstruction groups, respectively. The collected patient data included a preoperative and 2-year postoperative range of motion, visual analog scale scores, anterior stability tests, and clinical knee scores. Results: There were no significant differences in the 2-year postoperative range of motion, visual analog scale scores, or anterior stability tests. The Lysholm and International Knee Documentation Committee knee evaluation form scores were significantly higher in the early reconstruction group than in the elective reconstruction group. Conclusions: Early anterior cruciate ligament reconstruction is a more effective clinical knee score than elective reconstruction in treating anterior cruciate ligament tears.